Pengaruh Umur Perusahaan, Reputasi Auditor, Reputasi Underwriter Dan Persentase Penawaran Saham Terhadap Underpricing Pada Perusahaan Yang Melakukan Initial Public Offering (IPO) Di Bursa Efek Indonesia Tahun 2017-2019 - Iva Rinda Sari; Afi Rahmat Slamet; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determine the effect of company age, auditor reputation, underwriter reputation and percentage of shares offering on underpricing in companies that conduct an Initial Public Offering (IPO) listed on the Indonesia Stock Exchange (IDX) for the period 2017-2019. The method of analysis that used in this research was descriptive and multiple linear regression analysis. The population in this study was 148 companies that conducted an Initial Public Offering (IPO) listed on the Indonesia Stock Exchange (IDX) for the period 2017-2019. The sample selection technique used purposive sampling technique, so that 50 companies were obtained that matched the sample selection criteria. The results of this study indicate (1) Company age, auditor reputation, underwriter reputation and percentage of shares offering has a significant effect on underpricing (2) Company age has a negative and significant effect on underpricing (3) Auditor reputation has a negative and insignificant effect on underpricing (4) Underwriter reputation has a negative and significant effect on underpricing (5) Percentage of shares offering has a positive and insignificant effect on underpricing.Keywords: Company Age, Auditor Reputation, Underwriter Reputation, Percentage of Shares Offering, Underpricing